6.6k views
5 votes
Solve -9(t - 2) = 4(t – 15).
The solution is t=

2 Answers

2 votes

Answer:

6

Explanation:

-9t + 18 = 4(t-15)

-9 +18 = 4t - 60

-9t = 4t-60-18

-9t = 4t - 78

-9 - 4 = -78

-13 = -78t =

t = -78/-13

t = 6

User Stephenb
by
5.4k points
0 votes

Answer: t = 6

Step-by-step explanation: First we solve for -9(t-2) and that comes out to be -9t + 18. Then we solve for 4(t-15) which comes out to be 4t - 60. So the new equation we have is -9t + 18 = 4t - 60. In order to solve for t, we need to get t on one side of the problem by itself. To do this we will first add 9t to both sides and it comes out to be 18 = 13t - 60. t is still not by itself so now we add 60 to both sides and that gives us 78 = 13t. t is still not by itself so now we need to divide each side by 13 so that variable t is by itself. When we divide both sides by 13 we get 6 = t.

User MakingStuffs
by
5.8k points